The Impact of Corporate Governance Attributes on Tax Planning of Listed Deposit Money Banks In Nigeria: Corporate Governance and Tax Planning - Sallau, Muhammad Muhammad (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study examines the impact of corporate governance attributes specifically (Board size, Board composition and Audit committee size) on tax planning peroxide by effective tax rate of listed deposit banks in Nigeria. The population of the study consist of all the listed deposit money banks in Nigeria while using purposive sampling technique selected 7 listed DMB’s for a period of fourteen years (2008-2021), the data were obtained from the annual report and account of the sampled banks for the period. Ordinary least square was used to analyse the data using stata version 14. The study reveals that board size is negatively significant with effective tax rate. However, the regression results of board composition and audit committee size indicates that independent directors on the board have positive and significant impact on tax planning. While result for leverage and return on owners’ equity indicate that the two variables have insignificant relationship on tax planning. The result also shows that firm size measured as natural log of total asset is significant but negatively related with the tax planning. This implies that DMB’s have not been properly utilizing their assets in influencing their tax planning. Based on the above findings, this paper recommends that listed DMB’s should device a way of increasing corporate tax planning. The findings are limited to DMB’s listed on the floor of Nigerian Stock Exchange.